"NEW EDEN'' IN LITERATURE: IGNATIAN PEDAGOGY - G. Fajar Sasmita Aji (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Literature and pedagogy seem to be a coin of two faces. Since literature has the ultimate goal in preserving human civilization and pedagogy in humanizing civilization, the two play a very significant role in the creation ofqualitatively excellent characteristics to young participants ofeducation. So far the discussion on a piece of literary work is not interesting as the students commonly think that the study of literature is merely about an out dated text uplifting activities and people who are not real but imaginative. Moreover, sometimes the story is also dealing with the foreign culture. It is absolute that there is no practical benefit taken from such a study, and as a result students are not interested any more to achieve the ideal target in presenine human civilization, at least dealing with his/her own local wisdom. There is a strategy, called the Ignatian pedagogy, that may suggest the solution to the abole problem. lt provides a significant lole to students, and the positiirr of teacher transforms into the agent to consult due to the unsolved problems among the students. Therefore, there could be "New Eden" for the students to enjoy their study because the subject becomes enjoyable. The pedagogy covers some steps or elements to undergo and the main element is dealing about self-student's reflection and evaluation. To the concrete model, there is a given model on how lgnatian pedagogy can be applied into the lecture of Literature, especially in History of English Literature.